2013
DOI: 10.1186/1475-2867-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose etoposide-treatment induces endoreplication and cell death accompanied by cytoskeletal alterations in A549 cells: Does the response involve senescence? The possible role of vimentin

Abstract: BackgroundSenescence in the population of cells is often described as a program of restricted proliferative capacity, which is manifested by broad morphological and biochemical changes including a metabolic shift towards an autophagic-like response and a genotoxic-stress related induction of polyploidy. Concomitantly, the cell cycle progression of a senescent cell is believed to be irreversibly arrested. Recent reports suggest that this phenomenon may have an influence on the therapeutic outcome of anticancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 86 publications
2
28
0
3
Order By: Relevance
“…Our hypothesis, linking Unr-NRs to polyploidy, was correct since Unr-NRs were inducible in the hepatoblastic Hep3B cell line treated with etoposide, and in the trophoblastic BeWo cell line treated with Taxol (Litwiniec et al, 2013;Marth et al, 1995). Unr-NRs were preferentially formed in cells with enlarged nuclei, their frequency in the surviving cell population reaching up to 23% in etoposide-treated Hep3B cells and 70% in Taxol-treated BeWo cells.…”
Section: Unr-nrs Are Related To Both Stress and Polyploidymentioning
confidence: 78%
See 1 more Smart Citation
“…Our hypothesis, linking Unr-NRs to polyploidy, was correct since Unr-NRs were inducible in the hepatoblastic Hep3B cell line treated with etoposide, and in the trophoblastic BeWo cell line treated with Taxol (Litwiniec et al, 2013;Marth et al, 1995). Unr-NRs were preferentially formed in cells with enlarged nuclei, their frequency in the surviving cell population reaching up to 23% in etoposide-treated Hep3B cells and 70% in Taxol-treated BeWo cells.…”
Section: Unr-nrs Are Related To Both Stress and Polyploidymentioning
confidence: 78%
“…To this end, we selected two human cancer cell lines, BeWo and Hep3B − derived from trophoblasts and hepatocytes, respectively − to test the capacity of cytotoxic treatments known to induce polyploidy to trigger UnrNRs formation. The drugs we used included etoposide − a DNAdamaging drug, and Taxol − a spindle toxin (Litwiniec et al, 2013;Marth et al, 1995). Whereas Unr-NRs were detectable in untreated cultures, their incidence markedly increased following drug treatment in both cell cultures (Figs 5E and 6A).…”
Section: Unr-nrs Concentrate Poly(a) Rna Translation Factors and Ribmentioning
confidence: 99%
“…Therefore, it would be tempting to hypothesize that increased levels of cyclin D1 may somehow reflect or even promote these cells to enter the S phase and proliferate further, especially as we have shown in our cyclin D1/PI double staining experiment that the highest levels of cyclin D1 are indicative of G2/M population and particularly of the fraction of polyploid cells. In previous studies we also found that the levels/fluorescence of cyclin D1 increased in the G2/M and polyploidy after treatment with doxorubicin in the Jurkat and A549 cell lines ( _ Zury n et al, 2012; Litwiniec et al, 2013). The percentage of subG 1 Cyclin D1 after treatment with doxorubicin A.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be tempting to hypothesize that increased levels of cyclin D1 may somehow reflect or even promote these cells to enter the S phase and proliferate further, especially as we have shown in our cyclin D1/PI double staining experiment that the highest levels of cyclin D1 are indicative of G2/M population and particularly of the fraction of polyploid cells. In previous studies we also found that the levels/fluorescence of cyclin D1 increased in the G2/M and polyploidy after treatment with doxorubicin in the Jurkat and A549 cell lines (Żuryń et al, ; Litwiniec et al, ). The percentage of subG 1 fraction as well as early and late apoptotic cells, as evidenced by annexin V/PI staining, is visibly increased starting from this concentration and the number of G0/G1‐cyclin D1‐positive cells decreased, whereas the respective values were also reduced in the S‐ and G2/M‐phases with 0.3 µM doxorubicin, which suggests that induction of cell death pathways most probably contribute to observed reductions in the number of polyploid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies reported that higher doses of the compound (25–100 µM) activate apoptosis, mostly in a manner dependent on p53 [325,326,327,329]. Prolonged treatment at lower concentrations of ETP can also lead to induction of the p53 pathway, cell cycle arrest, senescence and apoptosis [145,325,330,335,337]. ETP induces the formation of irreversible DNA–TopoII cleavage complexes (TopoIIcc) and DNA damage regardless of concentration or incubation time [323,324,329,330,331,332,334,353].…”
Section: Compoundsmentioning
confidence: 99%